Plant life of a desert archipelago : flora of the Sonoran islands in the Gulf of California - Felger, Richard Stephen (Southwest Center series., 2012)
The desert islands of the Gulf of California are among the world's best-preserved archipelagos. The diverse and unique flora, from the cardón forests of Cholludo to the agave-dominated slopes of San Esteban, remain much as they were centuries ago, when the Comcaac (Seri people) were the only human presence in the region. Almost 400 plant species exist here, with each island manifesting a unique composition of vegetation and flora. For thousands of years, climatic and biological forces have sculpted a set of unparalleled desert worlds. This book offers in-depth coverage of the plants on islands in the Gulf of California found in between the coasts of Baja California and Sonora. The work is the culmination of decades of study by botanist Richard Felger and recent investigations by Benjamin Wilder, in collaboration with Sr. Humberto Romero-Morales, one of the most knowledgeable Seris concerning the region's flora. Their collective effort weaves together careful and accurate botanical science with the rich cultural and stunning physical setting of this island realm.